PENGARUH PENGETAHUAN KEWIRAUSAHAAN, KREATIVITAS KEWIRAUSAHAAN DAN MOTIVASI KEWIRAUSAHAAN TERHADAP KEBERHASILAN USAHA PADA USAHA MIKRO KECIL MENENGAH (UMKM) DI SURAKARTA (STUDI EMPIRIS PADA PELAKU UMKM) - Setya Apriyanti; Nursiam (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the influence of entrepreneurial knowledge, entrepreneurial creativity, and entrepreneurial motivation on business success in Micro, Small, and Medium Enterprises (MSMEs) in Surakarta. The Theory of Planned Behavior (TPB) approach is used to examine user behavior more comprehensively. The population in this study is 13,200 MSMEs in Surakarta, with a purposive sampling technique and the Slovin formula, a 10% error rate plus 12% oversampling, resulting in a sample of 112. Data analysis uses multiple linear regression accompanied by reliability, validity, and classical assumption tests. The results show that entrepreneurial knowledge has a positive and significant effect on business success. Entrepreneurial creativity is also proven to have a positive and significant effect on business success. In addition, entrepreneurial motivation does not have a positive and significant effect on business success. Keywords : Entrepreneurial Knowledge, Entrepreneurial Creativity, Entrepreneurial Motivation, Business Success. Micro, Small, and Medium Enterprises (MSMEs)